Cutaneous leishmaniasis: new oral therapeutic approaches under development. (12th September 2021) - de Souza, Myla Lôbo; dos Santos, Widson Michael; de Sousa, André Luiz Moreira Domingues; Ferraz, Leslie Raphael de Moura; da Costa, Lucas Amadeu Gonzaga; Silva, Emerson Oliveira; Rolim Neto, Pedro José
Abstract: The World Health Organization (WHO) classifies leishmaniasis as a disease for which the development of new treatments is a priority. Available drugs are not fully effective in all cases; they have parenteral administration and exhibit serious and common adverse effects. The only oral drug available (miltefosine) has shown resistance, is expensive, and is not available in many endemic countries. Thus, the development of an oral medicine may solve many of these issues. Based on that, this review aimed to investigate which therapeutic alternatives have been studied for the development of oral drugs for the treatment of cutaneous leishmaniasis. A literature search for keywords "leishmania and oral" was performed in PubMed and ScienceDirect, considering articles published in the last 5 years. The articles were selected based on the objective of the review. The main problem in the current treatment of leishmaniasis is the administration of injectables, since it requires patients to travel to health centers, hospitalization, and professional administration, conditions that are not adapted to the socioeconomic reality of patients. Therefore, many research studies have evaluated oral alternatives for the treatment of cutaneous leishmaniasis. The main tested approaches were obtaining new molecules, repositioning drugs, and new formulations of old drugs. The prospects are encouraging but still require more in vivo bioavailability and clinical trials.